2014
DOI: 10.2106/jbjs.m.01186
|View full text |Cite
|
Sign up to set email alerts
|

Primary Epiphyseal Osteomyelitis Caused by Mycobacterium Species in Otherwise Healthy Toddlers

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
(35 reference statements)
0
29
0
Order By: Relevance
“…At follow-up at a mean of 4.1 years, focal epiphyseal damage was present in 5 (62.5%) patients, and clinical growth disturbance was evident in 1 (12.5%) patient. 10 In light of this study, it can be concluded that growth disturbance is rare, but many osteitis patients need surgical intervention during the treatment of the infection. This finding is similar to the conclusions of our BCG osteitis study although our figures are lower, a leg length discrepancy in 6.9% and a minor gait abnormality in 1.3%.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…At follow-up at a mean of 4.1 years, focal epiphyseal damage was present in 5 (62.5%) patients, and clinical growth disturbance was evident in 1 (12.5%) patient. 10 In light of this study, it can be concluded that growth disturbance is rare, but many osteitis patients need surgical intervention during the treatment of the infection. This finding is similar to the conclusions of our BCG osteitis study although our figures are lower, a leg length discrepancy in 6.9% and a minor gait abnormality in 1.3%.…”
Section: Discussionmentioning
confidence: 77%
“…The study found that mycobacterial epiphyseal osteomyelitis seems to have an unfavorable clinical course that tends to lead to physeal damage. 10 In the 8 patients, the abscess was confined to the epiphysis at the time of initial presentation, but, over time, extended outside the epiphysis in 7 (87.5%) cases. Also, 7 patients needed surgical drainage, and 5 (62.5%) required additional surgery.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…gentle curettage and debridement under intraoperative fluoroscopy. In our literature review, fluoroscopy and endoscopy are used as to assist surgery to treat osteomyelitis of epiphyseal or physeal-involving lesions 15,16 . Endoscopic surgery under fluoroscopic guidance is reportedly useful for treating epiphyseal osteomyelitis caused by Mycobacterium species 17 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, for children, fragility fractures secondary to Graves' disease are a rare occurrence. The literature describing such fractures in children is limited to two case reports, including a distal radius fracture 3 and an oblique non-displaced femur fracture.…”
mentioning
confidence: 99%